The impact of the war on maintenance of long-term therapies in Ukraine - Khanyk, Nataliia; Hromovyk, Bohdan; Levytska, Oksana; Agh, Tamas; Wettermark, Björn; Kardas, Przemyslaw (Frontiers in Pharmacology, 2022)
Due to the Russian invasion, which started on February 24, 2022, the Ukrainian healthcare system is facing multiple challenges. A great number of healthcare facilities have been destroyed, while availability of other ones is often limited due to a lack of qualified medical staff. Certain services, e.g. cancer therapies, have been seriously disrupted. Moreover, millions of Ukrainians with chronic conditions are also suffering as due to war-related problems with execution of their long-term therapies. Availability of drugs is particularly limited in the occupied regions. According to the national statistics, as of August 18, 2022, about 505 pharmacies were destroyed in Eastern Ukraine and 47 completely ruined. Moreover, the invaders have been blocking humanitarian aid provided to these territories by the Ukrainian government or other countries. Fortunately, in the areas controlled by the Government of Ukraine, the acute shortage of medicines, observed at the beginning of the war, has already been eliminated. Nevertheless, not all drugs are now fully available, even in the areas where no military attacks occur. The economic availability of drugs is also profoundly influenced by the significant increase in the cost of medications and the fall in average salaries. The Government of Ukraine is trying to minimise the impact of these war-related challenges by adopting a new legislation. This includes, among others, simplification of procedures for licensing, quality control and import of medicinal products to Ukraine. Other measures involve securing displaced people with the option of benefiting from local healthcare facilities, broadening the the ePrescription [NOTE: truncated]